Report of Working Group on Agro-Climatic Regional Planning (ACRP) for the Formulation of IX Plan - Planning Commission (Planning Commission, 1996)
The Planning Commission initiated an exercise for undertaking agricultural development for achieving a rapid growth in agriculture defined in its comprehensive sense since the mid eighties. This was based upon the consideration that with the country achieving a reasonable measure of self-sufficiency in foodgrains, particularly the cereals, it was now conducive to plan for agricultural growth based on the agro-climatic and resource endowments of different areas and the availability of technologies for achieving rapid growth in production of a host of agricultural commodities.
Planning Commission
Planning Commission